Intercultural communication: a new approach to international relations and global challenges - Sadri, Houman A.; Flammia, Madelym (New York, 2011)
This introductory textbook approaches the study of intercultural communication from the field of international studies, focusing on issues of power, conflict, cooperation, and diplomacy. In our increasingly global world, the need for effective intercultural and international communication has become key for nations, groups, or individuals to move from conflict to cooperation and to resolve political power issues in a culturally diverse environment. In this text, the authors focus on the notion of mindful communication, which requires knowledge of diplomacy, politics, and economy as well as an understanding of cultural issues. After introducing key theories and concepts, the text examines the contemporary approaches to the study of intercultural communication before discussing processes and technologies. The last section looks at ethical issues relating to human rights, respecting cultures, and the role of intercultural communication in the future of the global community. Addressing undergraduate students in international relations, international studies, and intercultural communication, the book provides many examples drawn for world current affairs, politics, and diplomacy, from health care to the global financial crisis. Each chapter also features questions for review and further discussion, a case study exercise, and further references.
Keywords: Intercultural communication